Culture and organization (Routledge, 2009)
Culture and Organization features refereed articles that offer innovative insights and provoke discussion. It particularly offers papers which employ ethnographic, critical and interpretive approaches, as practised in such disciplines as communication, media and cultural studies, which go beyond description and use data to advance theoretical reflection. The Journal also presents papers which advance our conceptual understanding of organizational phenomena.